Study of the Expression Levels of Survivin Gene in Patients with Acute Myeloid Leukemia - Abbassy, Hadeer Aly; Elneely, Dalia Abdel Moety; Rahman, Ahmed Abdel; Ali Agram, Asmaa El Sayed El Araby Hassan (International Journal For Research In Health Sciences And Nursing, 2016)
Background: Acute myeloid leukemia (AML) is a genetically heterogeneous disease characterized by malignant clonal proliferation of immature myeloid cells. Survivin is a member of the inhibitor of apoptosis proteins (IAPs) gene family. It was found that knockdown of survivin was reported to induce apoptosis in leukemia cell lines and also potentiated the chemotherapeutic antileukemic effects. Aim: Investigating survivin gene expression levels in de novo acute myeloid leukemia at the time of diagnosis, and the correlation between survivin expression at time of diagnosis and the achievement of complete remission after induction chemotherapy. Materials and Methods: Real time quantitative polymerase chain reaction (PCR) was used and the results were evaluated with comparative Ct method for 35 AML cases controlled by 15 non AML patient. Results: The present study showed that Survivin expression was significantly higher in cases than in controls (p<0.001). The mean expression level of survivin among patients with complete remission (28.64 ± 6.23) was significantly lower than those with induction failure (186.86 ± 229.71) (p<0.001). None of AML cases with high expression of Survivin above the median achieved complete remission. The age of AML cases positively correlated to survivin gene expression (r= 0.615, p <0.001). Conclusion: Survivin expression analysis at time of diagnosis may aid in determining the prognosis of AML cases.